(3efJNH ef cJGH GdQMeI aj GdWHs - (3GdUHfQj , egOj Hf Ydj Hf EHQGgje Gdjefj GdegLej,J (B815 (3g` s
(3ChdgG (B:s
(3LejY GdCeQGV JMOK Yf aSGO GdeRGL haSGO GdeRGL jhf HaSGO CMO GdCNdGW GdCQHYI Ch HEKfjf efgG s
(3BNQgG (B:s
(3aef CMSf HGdChd CNQL GdOe hHGdKGfi CSgd GdShOG hGdKGdK GdUaQG hGdQGHY GdHdZe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3HgG fXGe GdJYbjHIs
(3HBNQgG aGFOg ai JOHjQ GdLeGYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B29s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP (B- (3YHO GdeMSf Hf MeO GdYHGO s
Keywords: (3GdWHs